Servicios públicos y remunicipalización - Tornos Mas, Joaquín (2016)
It is difficult to define the legal concept of public service. There are two ways to understand it. The first one is objective and tries to determine which activities and services should be guaranteed to all citizens with the aim of social cohesion. The second one is subjective and is based on the idea that public services are activities excluded from the market. This second conception emphasizes the problems arising from the relationship between the public and private sectors rather than the right of the citizenship to receive specific services. Within this general conceptual framework, this work shows the current debate which is not centered on which kinds of public services are to be provided but rather on how they have to be provided. The debate has a strong ideological content and defends the return to public management at the expense of private management, which is considered inefficient. This work analyzes the debate and introduces some objections to remunicipalization.